Pemanfaatan Limbah Kulit Buah Matoa (Pometia Pinnata) Sebagai Obat Kumur Herbal Solusi Pencegah Karies Gigi - Mahdalena Sy. Pakaya; Nazwah Buana Putri Kalangi; Santi Santi; Nurdiandra Jahja; I Made Hariadi Wijaya; Fajar Dwi Agung (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2021)
Dental health problems are a common problem for the entire world population, including Indonesia. The incidence of dental caries worldwide has a fairly high number, namely 80-90% in children under 18 years. One of the main factors causing dental caries is the presence of caries-causing bacteria, namely Streptococcus mutans which is a normal flora of the oral cavity. The type of business that will be made is the production and marketing business of mouthwash with the composition of extracts from the waste of the matoa fruit peel as a solution in overcoming dental caries. Based on research by Kai (2021), where the results of the potency test of matoa fruit peel extract against Streptococcus mutans bacteria showed concentrations of 25%, 50%, and 75% with the resulting inhibition zones of 11.75 mm, 15.82 mm and 18.75. This mouthwash formulation consists of Matoa Fruit Peel Extract, Sorbitol, Glycerin, Sodium Benzoate, Aquadest, and Pipermint. This product has promising business prospects because there are no similar products on the market, the basic ingredients are easy to get and in terms of financial analysis and business feasibility, an overview of the planned business can get promising profits